Educational Research Methodology Trends of Southeast Asia English Major Undergraduate Theses: A Content Analysis - Maulina, Maulina; Dayana, Umil; Nasrullah, Rahmat; Geelan, David; Ordanza Cortez, Angelica (AL-ISHLAH: Jurnal Pendidikan, 2024)
The present study thoroughly examines the predominant research methodology trends and topics applied in a specific time frame from 2019 to 2023 in educational research of the online searchable undergraduate theses in English major programs across Southeast Asia, utilizing a comprehensive content analysis approach. By employing keyword extraction, topic-specific modelling, and thematic evaluation, our objective is to ascertain the prevailing methodologies in English language teaching and the research interest themes from 347 undergraduate downloadable theses that have been investigated. The analysis explores the possible ramifications of these patterns on the caliber of undergraduate research, English language instruction, and the broader education domain within the given area. This study revealed a strong preference (54.5%) for quantitative approaches, highlighting the importance of empirical methodologies. Additionally common were qualitative approaches (24.8%), suggesting an increasing recognition of the importance of examining human factors. While action research (8.4%), particularly Classroom Action Research (CAR), was less prevalent than mixed-method approaches (12.8%), this suggests that action research needs to be recognized. The different ratios of research methods demonstrated a dedication to investigating various questions and advancing knowledge in language, literature, and education. The interesting research themes identified the complex and diverse nature of English language raising focus in Southeast Asia such as technological integration, teacher development, cultural studies, assessment, and language teaching methodologies. The study provides useful information for enhancing research mentorship and education, and it improves knowledge of research trends in this setting. Furthermore, the findings obtained from this study have the potential to contribute to the enhancement of curriculum design, instructional approaches, and distribution of resources in the English language education research area.